Reverse remittances as a new normal for Ukraine: evidence from Germany and Austria - Taras Romashchenko (Forced Migration Review, 2024)
The Russian invasion has prompted a new phenomenon: significant reverse remittances from within Ukraine to displaced Ukrainians in other countries (Germany and Austria in particular). This has implications for the individual recipients, host countries, and for Ukraine itself.
Keywords: 300; reverse remittances; Ukraine; Germany; Austria; refugees; forced migrants